Pengaruh Jiwa Kewirausahan dan Karateristik Kewirausahaan Terhadap Keberhasilan Usaha Salon di Pangkalan Balai - Ipana Ipana; Dian Utari (P3M STIE Mulia Darma Pratama, 2020)
Becoming an entrepreneur today, is not just being able to start and set up a business just like that, but to be guided to be able to direct his business to a state that continues to be profitable and gain a sustainable or continuous competitive advantage over competitors. Therefore, let us not ever start a business by trial and error without having a clear direction and purpose because often the consequences will be very detrimental if there are mistakes that were not calculated beforehand. So we need an attitude that is able to face every possibility that occurs in running a business by holding on to the beliefs and abilities of reliable individuals. So, entrepreneurs need abilities and clear goals, what to achieve and how to achieve them. The formulation of the problem in this research is, How is the entrepreneurial spirit in the success of the salon business in Pangkalan Balai ?, What are the characteristics of entrepreneurship on the success of the salon business in Pangkalan Balai? Is there a partial influence of entrepreneurial spirit and entrepreneurial characteristics on the success of the existing salon business at Pangkalan Balai? And is there a simultaneous influence of an entrepreneurial spirit and entrepreneurial characteristics on the success of the salon business in Pangkalan Balai? The populations in this study were 30 salons in Pangkalan Balai. The results in this study that the Entrepreneurial Spirit Variable (X1) has a significant effect on Business Success (Y). The results obtained by tcount is 3,280 with a significant value of 0.001, tcount (3,280)> ttable (1.703) and a significant value of 0.003 <0.05, Characteristics variable Entrepreneurship (X2) has a significant effect on business success (Y), the results obtained by tcount is 4.269 with a significant value of 0.000, tcount (4.269) > ttable (1.671) and a significant value of 0.000> 0.05, the entrepreneurial characteristics variable (X2) has a significant effect on business success (Y), the results obtained tcount of 4.269 with a significant value of 0.000, tcount (4.269)> t table (1.671) and a significant value of 0.000> 0.05.